Hospital leadership perspectives on the value of the 3 Wishes Project: a qualitative study. Issue 2 (27th October 2020) - Swinton, Marilyn; Vanstone, Meredith; Phung, Peter; Neville, Thanh H; Takaoka, Alyson; Smith, Orla M; Baker, Andrew; LeBlanc, Allana; Foster, Denise; Dhingra, Vinay; Clarke, France J; Hoad, Neala; et al.
Abstract : Background: Healthcare organisations are increasingly interested in improving the work life of their employees. By encouraging individualised acts of compassion for dying patients and their families, the 3 Wishes Project (3WP) has been shown to ease grief for both families and clinicians. Purpose: The objective of this study was to explore the perspectives of hospital leaders on the value of the 3WP to the hospital and how decisions are made about which programmes to support. Methods: We conducted semistructured interviews with 20 hospital leaders in four North American institutions. Transcripts were analysed using qualitative content analysis. Results: Interviews with 12 clinical managers and 8 senior administrators identified the institutional value of the 3WP as improving patient and family experiences, enhancing staff morale, translating institutional mission and values into front-line practice, and creating positive public relations. Hospital leaders acknowledged potential resource challenges, including staff time, space to store supplies and funds to purchase items for some wishes. However, citing stories they had heard from families and staff, hospital leaders shared their view of how their decisions about the value of clinical programmes extend beyond quantifiable outcomes. Conclusions: When reflecting on this personalised palliative care programme, hospital leaders described how inspiring narratives promoted institutional values in ways that are difficult to measure quantitatively. Leaders underscored the need to balance the value that a programme brings with the resources it requires, stating how different types of evidence influence their support of new programmes. Trial registration number: NCT04147169 .